Setting the weights of sustainability criteria for the appraisal of transport projects - Cadena, Paola C. B.; Magro, José Manuel Vassallo (Transport, 2015)
Although the Multi-Criteria Decision Analysis (MCDA) has made progress towards appraising and measuring the performance of smart and sustainable transport projects, it still has important issues that need to be addressed such as the problem associated with incomparable quantities, the inherent subjective qualitative assessment, the complexity of identifying impacts to be included and its measurement method, and the corresponding weights. The issue of trading-off different sustainability criteria is the main unresolved matter. This problem may lead to lack of accuracy in the decision making process. This paper presents a new methodology to set the weights of the sustainability criteria used in the MCDA in order to reduce subjectivity and imprecision. We suggest eliciting criteria weights based on both expert preferences and the importance that the sustainability criteria have in the geographical and social context where the project is developed. This novel methodology is applied to a real case study to quantify sustainable practices associated with the design and construction of a new roadway in Spain. The outcome demonstrates that the approach to the weighting problem has significance and general application in a multi-criteria evaluation process.